2007
DOI: 10.1007/s11055-007-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of the pattern of cortical activation in the phase structure of the human EEG

Abstract: A total of 22 healthy subjects in the EEG laboratory and 62 patients in the clinical functional diagnostic unit were studied. Spontaneous EEG recordings were made using the 10-20 scheme relative to combined ear electrodes in the state of rest with the eyes closed and open and during various functional loads. Traces were analyzed by computer animation of the EEG phase structure. The main concept of the method for extracting phase structure was based on not using a single reference lead. Time shifts were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…1, A), moving them closer together than usual. Previous studies [Belov et al, 2004a, Belov et al, 2004bGetmanenko et al, 2006] have shown that the optimum interelectrode interval is 2.5-3 cm. EEG traces were made using a monopolar scheme relative to combined ear electrodes.…”
mentioning
confidence: 97%
“…1, A), moving them closer together than usual. Previous studies [Belov et al, 2004a, Belov et al, 2004bGetmanenko et al, 2006] have shown that the optimum interelectrode interval is 2.5-3 cm. EEG traces were made using a monopolar scheme relative to combined ear electrodes.…”
mentioning
confidence: 97%